Headstarting Turtles—More Food for Thought - Forrester, Harriet (Wildlife Rehabilitation Bulletin, 2008)
A recently published article, Headstarting Turtles—Another Perspective (Bogard 2007) presented a different viewpoint and referred to three turtle recovery projects, and made other points, as support for headstarting. The information presented here gives more food for thought on the subject.